Cytokinins – regulators of de novo shoot organogenesis - Šmeringai, Ján; Schrumpfová, Petra Procházková; Pernisová, Markéta (Frontiers in Plant Science, 2023)
Plants, unlike animals, possess a unique developmental plasticity, that allows them to adapt to changing environmental conditions. A fundamental aspect of this plasticity is their ability to undergo postembryonic de novo organogenesis. This requires the presence of regulators that trigger and mediate specific spatiotemporal changes in developmental programs. The phytohormone cytokinin has been known as a principal regulator of plant development for more than six decades. In de novo shoot organogenesis and in vitro shoot regeneration, cytokinins are the prime candidates for the signal that determines shoot identity. Both processes of de novo shoot apical meristem development are accompanied by changes in gene expression, cell fate reprogramming, and the switching-on of the shoot-specific homeodomain regulator, WUSCHEL. Current understanding about the role of cytokinins in the shoot regeneration will be discussed.